A fiber-reinforced human-like soft robotic manipulator based on sEMG force estimation. (November 2019) - Feng, Naishi; Wang, Hong; Hu, Fo; Gouda, Mohamed Amin; Gong, Jiale; Wang, Feng
Abstract: Before the myoelectric prosthesis become a good substitute of a natural arm, there still exist several big challenges in terms of hand structural design and control algorithms. The overall objective of this paper is to propose a new humanoid hand with specify force output under sEMG control. A fiber reinforced three-cavity structure is proposed with thumb and middle finger bendable and the rest of the fingers bendable and twistable simultaneously to imitate the finger-to-finger function. The relation between the input pressure and twist angle is derived based on the material mechanics formula and the neo-Hookean model. The force module of the soft hand and sEMG are built achieving the accuracy of 94.2%. The experimental result has supported that the developed soft hand can be applied to artificial limb improving the quality of amputee's life.